Determination of the pole and (MS)over-bar masses of the top quark from the t(t)over-bar cross section - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (Elsevier B.V., 2011)
We use higher-order quantum chromodynamics calculations to extract the mass of the top quark from the t (t) over bar cross section measured in the lepton + jets channel in p (p) over bar collisions at root s = 1.96 TeV using 5.3 fb(-1) of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron Collider. The extracted top quark pole mass and (MS) over bar mass are compared to the current Tevatron average top quark mass obtained from direct measurements. (C) 2011 Elsevier B.V. All rights reserved.